Physical violence and its associations: Insights from nationally representative data in India - Monisha Mary P; Ankeeta Menona Jacob; Avinash K Shetty (Women's Health)
Background: Empowerment is vital for individuals’ control over their lives but is often constrained for women in India due to deep-rooted patriarchal norms. This affects health, and resource distribution, and increases domestic violence. Domestic violence including physical, sexual, emotional, economic, and psychological abuse is a significant human rights and public health issue. Understanding the link between women’s empowerment and attitudes toward physical violence is essential for addressing this problem. Objectives: To explore the relationship between various aspects of women’s empowerment and their attitudes toward the justification of physical violence in specific circumstances. The study aimed to provide insights into how empowerment can serve as a protective factor against domestic violence. Design: A cross-sectional study was conducted using the data from the National Family Health Survey-5 (NFHS-5), collected from 2019 to 2021. The study was carried out between July 2023 and March 2024. Methods: Data from NFHS-5, focusing on women aged 15–49 who completed the domestic violence module, were analyzed. Women’s empowerment was measured through employment, asset ownership, and decision-making autonomy. The study assessed 8 indicators of employment, 12 of asset ownership, 9 of decision-making, 5 justifying physical violence, and 11 indicators of physical abuse. Frequencies, percentages, Fischer’s exact test, and logistic regression were used, with significance set at p  < 0.05. Results: Of 4562 women, 23 (0.7%) were employed, 3397 (74.5%) owned mobile phones, and 744 (21.9%) used them for transactions. Joint financial decisions were made by 2692 (75.2%) couples. Restrictions on meeting friends were reported by 376 (10.1%), and 431 (11.6%) had trust issues with partners. Physical violence was justified by 934 (20.5%) for neglecting children, and 3365 (90.4%) experienced partner violence. Land ownership was reported by 383 (8.4%) women. Empowered women were less likely to justify or experience violence, with mobile phone use and decision-making autonomy linked to reduced violence. Conclusion: Women’s empowerment through employment, asset ownership, and decision-making is associated with reduced justification and prevalence of physical violence. Despite progress, entrenched societal norms persist. Interventions should focus on economic and social empowerment, addressing cultural attitudes and promoting gender equality.